Construction of community home-based older adult care service model based on modular design concept - Zhou, Xiaohua; Chen, Lina; Lou, Xu; Li, Ying; Han, Bobo (Frontiers in Public Health, 2025)
ObjectvieTo address the supply–demand mismatch in community home-based older adult care services amid China’s deepening aging population crisis.MethodsThis study employs a modular design concept, selecting Liaoning Province—the region with the nation’s highest aging rate—as the research area. A questionnaire survey was conducted among 331 community-dwelling older adults, and multiple linear regression analysis was applied to identify factors influencing care service demands.ResultsKey findings include: (1) Older adult’ demands manifest a five-dimensional structure (life assistance, medical care, spiritual/cultural engagement, rights protection, and age-friendly modifications), with spiritual/cultural engagement (score rate: 68.40%) and age-friendly modifications (67.67%) being the most urgent needs. (2) Subgroups including advanced age (≥71 years), disabled, living alone, highly educated, and chronic disease individuals exhibited significantly higher demand intensity (p < 0.05). For instance, the regression coefficient (B) for medical care demand among the disabled reached 0.545. (3) Based on these results, a modular service framework was constructed, featuring five functionally independent core modules. A dynamic service package combination function was innovatively proposed, utilizing a module activation coefficient (αk,i) and an module weighting factor (βk,i) to achieve precise customization.ConclusionCentered on community residents’ committees (CRCs) as coordination hubs, this model enables dynamic monitoring and optimization through the Demand-Service Matching Index (DSMI), offering an actionable solution to reconcile fragmented resources and heterogeneous demands, thereby supporting both older adults and their caregivers in regional older adult care systems.